2018
DOI: 10.1016/j.celrep.2017.12.088
|View full text |Cite
|
Sign up to set email alerts
|

The Wiskott-Aldrich Syndrome Protein Contributes to the Assembly of the LFA-1 Nanocluster Belt at the Lytic Synapse

Abstract: T lymphocyte cytotoxicity relies on a synaptic ring of lymphocyte function-associated antigen 1 (LFA-1), which permits polarized delivery of lytic granules. How LFA-1 organization is controlled by underlying actin cytoskeleton dynamics is poorly understood. Here, we explored the contribution of the actin cytoskeleton regulator WASP to the topography of LFA-1 using a combination of microscopy modalities. We uncover that the reduced cytotoxicity of Wiskott-Aldrich syndrome patient-derived CD8 T lymphocytes lacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…Finally, it is possible that WASP itself plays a role. Indeed, a recent super-resolution imaging study demonstrated that WASP promotes degranulation close to regions of integrin clustering (46), implying a role for the protein in granule targeting.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is possible that WASP itself plays a role. Indeed, a recent super-resolution imaging study demonstrated that WASP promotes degranulation close to regions of integrin clustering (46), implying a role for the protein in granule targeting.…”
Section: Discussionmentioning
confidence: 99%
“…Local Ca 2+ influx, which drives regulated fusion at the neuronal synapse (Sudhof, 2012), could also be involved. Finally, recent studies have suggested that granule docking and fusion occur close to areas of strong integrin engagement (Houmadi et al, 2018), implying that outside-in signal transduction or mechanical tension could define permissive locations for exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Close coordination between the centrosome and F-actin dynamics could facilitate the efficient organization of synaptic output in space and time. Recent studies suggest that degranulation occurs in synaptic domains that are enriched in LFA1 and that are actively transmitting force against the target cell(Houmadi et al, 2018;Tamzalit et al, 2019). It will be interesting to investigate the role of the centrosome in ensuring this spatial coupling.…”
mentioning
confidence: 99%
“…Within seconds, T cells seeded onto an APS spread to form a symmetric contact interface ( Figure S1). Symmetric synapses persisted for ~10 minutes, followed by a transition period when the cells began polarizing and becoming motile (Hons et al, 2018;Houmadi et al, 2018;Mayya et al, 2018;Negulescu et al, 1996), reflected in an increase in AR ( Figure 1B, Videos S1-2). Structured illumination microscopy (SIM) revealed the presence of peripheral actin-rich lamellipodia and punctate actin structures distributed across the synaptic interface ( Figure 1C) -termed 'actin foci' -that are formed at TCR microclusters upon TCR triggering.…”
Section: Synapse Maintenance During T Cell Activation Is Associated Wmentioning
confidence: 99%
“…To model synapse formation and eventual disengagement we seeded mouse primary naïve CD4 + primary T cells (referred to as 'T cells' henceforth) onto an anti-CD3/intercellular adhesion molecule-1 (ICAM-1)-coated coverslip (antigen presenting surface, APS) and allowed synapses to form. We then assessed cellular polarization over time (by recording the cells' morphologic aspect ratio, AR) to detect T cells breaking their synaptic contact, because the contact interface shape is tightly linked to the motility state of the T cell (Hons et al, 2018;Houmadi et al, 2018;Mayya et al, 2018;Negulescu et al, 1996) (Figure 1A, Figure S1-2); Synapses are radially symmetric in their stable state, and polarize to break symmetry and acquire an elongated morphology prior to motility resumption (Videos S1-2).…”
Section: Synapse Maintenance During T Cell Activation Is Associated Wmentioning
confidence: 99%